Evolutionarily conserved modules in actin nucleation: lessons from Dictyostelium discoideum and plants. Review article - Cvrcková, F; Rivero, F; Bavlnka, B (Protoplasma, 2004)
The actin cytoskeleton plays a central part in the dynamic organization of eukaryotic cell structure. Nucleation of actin filaments is a crucial step in the establishment of new cytoskeletal structures or modification of existing ones, providing abundant targets for regulatory processes. A substantial part of our understanding of actin nucleation derives from studies on yeast and metazoan cells. However, recent advances in structural and functional genome analysis in less traditional models, such as plants or Dictyostelium discoideum, provide an emerging picture of an evolutionarily conserved core of at least two actin nucleation mechanisms, one mediated by the Arp2/3 complex and the other one by the formin-based module. A considerable degree of conservation is found also in the systems controlling the balance between filamentous and globular actin (profilin, actin-depolymerizing factor/cofilin) and even in certain regulatory aspects, such as the involvement of Rho-related small GTPases. Identification of such conserved elements provides a prerequisite for the characterization of evolutionarily variable aspects of actin regulation which may be responsible for the rich morphological diversity of eukaryotic cells.
Keywords: proteiny huseníčku; Profilins; Actin Cytoskeleton; výměnné faktory guaninnukleotidů; aktiny; Biological Evolution; Models, Biological; Rho proteiny vázající GTP; mikrofilamentové proteiny; Arabidopsis Proteins; zvířata; Arabidopsis; Actin Depolymerizing Factors; Cytoskeletal Proteins; faktory depolymerizující aktin; cytoskeletální proteiny; Contractile Proteins; biologická evoluce; profiliny; protein 2 související s aktinem; biologické modely; rho GTP-Binding Proteins; kontraktilní proteiny; Dictyostelium; Actin-Related Protein 2; Microfilament Proteins; Actins; Animals; Guanine Nucleotide Exchange Factors; mikrofilamenta